2020
DOI: 10.15837/ijccc.2020.4.3901
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Model for Ultra-Short-Term Output Power of Wind Farms Based on Deep Learning

Abstract: The output power prediction of wind farm is the key to effective utilization of wind energy and reduction of wind curtailment. However, the prediction of output power has long been a difficulty faced by both academia and the wind power industry, due to the high stochasticity of wind energy. This paper attempts to improve the ultra-short-term prediction accuracy of output power in wind farm. For this purpose, an output power prediction model was constructed for wind farm based on the time sliding window (TSW) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Summarizing the researchers' work, we found that the wind energy hybrid prediction framework consists of four main steps: data pre-processing, predictor prediction, error post-processing, and model performance evaluation. The technologies that may be used in the entire forecasting process can be divided into 10 categories: denoising, outlier detection and correction, resampling, normalization, decomposition, feature engineering, residual error modelling, filter-based correction, predictor and optimization algorithm [7,11,[140][141][142]. There has been a detailed review of these technologies by scholars, and we will not repeat them here.…”
Section: Discussion and Future Directionmentioning
confidence: 99%
“…Summarizing the researchers' work, we found that the wind energy hybrid prediction framework consists of four main steps: data pre-processing, predictor prediction, error post-processing, and model performance evaluation. The technologies that may be used in the entire forecasting process can be divided into 10 categories: denoising, outlier detection and correction, resampling, normalization, decomposition, feature engineering, residual error modelling, filter-based correction, predictor and optimization algorithm [7,11,[140][141][142]. There has been a detailed review of these technologies by scholars, and we will not repeat them here.…”
Section: Discussion and Future Directionmentioning
confidence: 99%
“…(BPNN) [12,13], support vector regression (SVR) [14][15][16][17] and the deep learning network [18,19]. Wind power has the characteristics of a time series and has strong non-linearity.…”
Section: Lstm Model Structurementioning
confidence: 99%
“…Statistical methods establish a model that can express the mapping relationship between input and output by mining the inherent laws between a large number of historical data [8]. Commonly used statistical methods include time series analysis [9][10][11], the BP neural network (BPNN) [12,13], support vector regression (SVR) [14][15][16][17] and the deep learning network [18,19]. Wind power has the characteristics of a time series and has strong non-linearity.…”
Section: Introductionmentioning
confidence: 99%
“…Literature [6] proposed a photovoltaic power prediction method combining Support Vector Regression (SVR) and Kalman filter, but inaccurate parameter selection of SVR resulted in reduced prediction accuracy. Literature [7] combined the cuckoo search algorithm with SVR to enhance parameter selection yet failed to consider the missing data and abnormal cases. In literature [8], a BP neural network was optimized using the Sparrow Search Algorithm (SSA) to establish an SSA-BP PV power prediction model.…”
Section: Introductionmentioning
confidence: 99%